The Effects of Customer Trust, Service Quality, and Product Quality on Customer Loyalty: The Mediating Role of Customer Satisfaction at Rindah Catering - Ananda Rendita Putri; Sugiyanto Sugiyanto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Competition in the food and beverage service industry, particularly in the catering sector, has intensified as consumers increasingly demand food services that are practical, hygienic, and of high quality. This study aims to examine the effects of customer trust, service quality, and product quality on customer loyalty through customer satisfaction at Rindah Catering. The sample was selected using a purposive sampling technique, consisting of customers who had placed orders with Rindah Catering within the previous three months, were at least 18 years old, and resided in Tangerang Regency. A total of 180 respondents participated in the study. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that customer trust has no significant effect on either customer satisfaction or customer loyalty. Product quality has a positive effect on customer satisfaction but does not significantly influence customer loyalty. Similarly, service quality has a positive effect on customer satisfaction but does not directly affect customer loyalty. Furthermore, customer satisfaction mediates the relationship between customer trust and customer loyalty. These findings suggest that customer satisfaction plays a crucial role in fostering customer loyalty within the catering industry. Practical implications for Rindah Catering include maintaining friendly and professional communication, providing clear and patient explanations, offering guarantees and demonstrating accountability, understanding customer needs rather than focusing solely on sales, expressing appreciation even when handling complaints, responding to complaints promptly and effectively, listening attentively to customers, selecting high-quality ingredients, ensuring food freshness, and storing ingredients under appropriate temperature conditions.